POTRET PERJALANAN HUKUM ISLAM DI INDONESIA - Hendra Gunawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
Islamic law landed in Indonesia, under Arab merchants and developed by the sultanate or Islamic empire in Indonesia began the kingdom of Samudera Pasai in Aceh to the Islamic empire in Eastern Indonesia which until finally until now Islamic law also influence the legal system of Indonesia, namely Islamic law of Indonesia which has colored various local cultural views typical of the archipelago to make Islamic law in Indonesia to grow and dynamic in accordance with the development of Indonesian society.Historically, Islamic law has taken a long road in Indonesia from pre-independence to the present even though it has been a collision of Western European law brought in the Dutch colonial, until the Islamic law which concerns criminal disappeared and not so taste in Indonesia, so in this writer want to decipher the portraits of Islamic jurisprudence on our beloved Pancasila earth that experience the dim light from phase to phase.